The Representation of White Supremacy in Colson Whitehead‘s The Nickel Boys - Utami, Evi Setyo Budi; Pramita, Agry; Hkikmat, Mahi M (Journal of English Language and Education, 2025)
This study aims to explain the forms of white supremacy in the novel The Nickel Boys by Colson Whitehead. The theory used in this research is Fredrickson's theory of white supremacy. This study was used descriptive qualitative research.This research analyzes the dialogue and narration in the novel as a whole. Supported by Stuart Hall's representation theory illustrates that this novel represents events in America in the 1960s regarding white supremacy based on social problems arised. This study's findings show that three forms of white supremacy are represented in the novel. Color bar reflects the inequality in American multiracial society depicted in the novel. Racial segregation refers to the separation of communities based on different races and skin colors that identify blacks and whites are separated in the school. Restriction is a combination of the two concepts, color bar and racial segregation, which ultimately causes people of color and blacks not to obtain equal rights with whites.